2016
DOI: 10.1002/imhj.21565
|View full text |Cite
|
Sign up to set email alerts
|

Home Visit Quality Variations in Two Early Head Start Programs in Relation to Parenting and Child Vocabulary Outcomes

Abstract: Home‐visiting programs aiming to improve early child development have demonstrated positive outcomes, but processes within home visits to individual families are rarely documented. We examined family‐level variations in the home‐visiting process (N = 71) from extant video recordings of home visits in two Early Head Start programs, using an observational measure of research‐based quality indicators of home‐visiting practices and family engagement, the Home Visit Rating Scales (HOVRS). HOVRS scores, showing good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 80 publications
1
45
0
1
Order By: Relevance
“…In an analysis of two Early Head Start programs, Roggman et al. () showed that HOVRS ratings relate to some elements of program quality (family involvement), but not to others (amount of program contact).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an analysis of two Early Head Start programs, Roggman et al. () showed that HOVRS ratings relate to some elements of program quality (family involvement), but not to others (amount of program contact).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Roggman et al. (), for example, has suggested that home visitors who were observed to engage in higher quality practice had families with higher parenting and child language scores. Peterson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of stability in this study could underscore the complexity of enhancing quality over time. Recent research has demonstrated the interface of quality (i.e., the HOVRS) with home‐visitors’ strategies (i.e., observing, modeling, coaching parent–child interactions) as well as with the duration of joint, child‐development‐focused activity involving home visitors, parents, and children (Peterson et al., 2018; Roggman et al., ). Two implications emerge from these collective findings.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has taken a detailed view of the links between the quality of home visitor–parent alliances and child outcomes, demonstrating that higher quality breeds effective home‐visiting practices for promoting parenting that effectively facilitates children's development (Roggman et al., ). Peterson et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation